Diseño de un banco de pruebas didáctico para el análisis de una transmisión automática (2018)
This project started with the research about the automatic transmissions, with the information that was obtained, the design of a transmission was processed as the transmission A130 of Toyota, in the design took into account the factors that influenced the design as for example, the fact of being didactic and printed in 3D, the dimensions were taken based on the manual of the transmission A130 and the simulation of finite elements was carried out using the NX software of the critical parts and the structure of the bench.